Faktor-Faktor yang Berhubungan dengan Kejadian Abortus di Rumah Sakit Muhammadiyah Palembang Tahun 2020 - Khofifah Farawansya; Pradiva Dwi Lestari; Merisa Riski (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
WHO the incidence of abortion is ±10-15% of 6 million pregnancies. Abortion is the expulsion of products of conception that occurs at gestational age < 20 weeks and fetal weight ≤ 500 grams. Factors causing abortion are parity, maternal age, abortion history, education level and gestational gap. There are also other affecting factors, namely the predisposition to repeated abortions. The possibility of repeated abortions in a woman who has had abortions is three times or more. The goal of this study was to determine the relationship of parity, maternal age and gestational gap simultaneously with the incidence of abortion at Muhammadiyah Hospital Palembang in 2021. The design of this study used the analytical survey method with the Cross Sectional approach. The population in this study included all pregnant women with 0-6 months of gestation who came to examine their pregnancies at Muhammadiyah Hospital Palembang in January-May 2021, with the total of 718 people. Sampling technique was the Systematic Random sampling with the total samples of 88 respondents. Data analysis used the univariate analysis and bivariate data analysis. The results of the study showed that there was a relationship between parity (Pvalue = 0.040) and maternal age (Pvalue = 0.036) and there was no relationship between gestational gap (Pvalue = 0.059) with the incidence of abortion at Muhammadiyah Hospital Palembang in 2021. It is expected that the results of this study can be an overview for the health services workers to upgrade the quality of health, especially dealing with the incidence of abortion.